Study of psycho-social impairment in patients presenting with age related macular degeneration in a tertiary eye care hospital - Danayak, Parul; Jani, Chinmay; Verma, Anita; Shah, Parth (International Journal of Research in Medical Sciences, 2017)
Background: Age Related Macular Degeneration (ARMD) is an eye condition affecting old age people causing severe vision loss. This study was carried out to assess the psycho-social impairment in the ARMD patients and compare it with the normal eye patients. Methods: A Two study groups were made: 1. ARMD patients. 2. Control group patients. Patients of both the groups were made to fill “The validated Gujarati version of: General Health Quality Questionnaire-28 (GHQ 28)”. Self-scoring was done according to 0-1-2-3 lower to higher disability respectively. Results: Prevalence GHQ Mean score of ARMD patients was 34.27 and that of normal eye patients was 24.66. 80.85% of ARMD patients and 26.73% of normal eye patients were psychosocially impaired. Conclusion: ARMD patients are psychosocially more impaired as compared to control group patients (p value <0.001, highly significant).